The new realities : - Drucker, Peter F. (Harper & Row, 1989)
Management guru Drucker discusses some political realities--the governmental and political process, the economy, ecology, economics, and the new knowledge society--in a way only he can. These realities are identified and discussed in order to suggest what we should be thinking about today in order to prepare for tomorrow. Clearly there are limits on what government can do, and there needs to be a rethinking of contemporary economics. Citing from classical as well as contemporary sources, Drucker has brought together a work that will force its readers to think. Recommended for all collections.